Analysis of Geometrical and Process‐Related Parameters on the Impregnation Quality of Advanced Cellular Composites1 . Issue 10 (10th April 2017) - Weißenborn, Oliver; Geller, Sirko; Gude, Maik
Abstract : Based on the well‐established polyurethane (PUR) spray coat method, an integral manufacturing process is developed to simultaneously create textile‐reinforced top and bottom layers as well as the cellular core in one single production step for advanced sandwich structures. Since the foaming matrix impregnates the textile layers during expansion and also serves as core material in the final part, these sandwich elements are connected cohesively with each other. Within this paper, impregnation studies are conducted to evaluate the influence of process parameters, such as mold temperature and dwelling time of the foam matrix, as well as part geometry and foam density on the local yarn impregnation. Evaluation of cell morphology is performed by measuring the cell size distribution inside impregnated yarns. Abstract : Novel processing technologies for smart design concepts of structural lightweight parts are of high relevance for industrial applications. In this context, the PUR spray coat method is used to impregnate carbon fiber textiles with a cellular matrix material by using the expansion reaction of PUR rigid foams. The influence on the local impregnation quality and composite morphology is investigated comprehensively.